2017
DOI: 10.1017/s1368980017002786
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the design, implementation and effectiveness of mass media and nutrition education interventions for infant and young child feeding

Abstract: Despite evidence of effectiveness, few common elements in the design of interventions were identified. Future research should consistently report these details to open the 'black box' of IYCF interventions, identify effective design components and ensure replicability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 45 publications
(351 reference statements)
5
78
0
2
Order By: Relevance
“…Our findings are consistent with other studies that have found a positive impact of mass media and BBC campaigns on IYCF practices (Graziose et al, ; Lee et al, ; Naugle & Hornik, ). Monterrosa et al () found increases in the consumption of leafy greens, thicker broth, and beef after the scripted message intervention, which was delivered by vaccination nurses and on local radios, was implemented in Mexico.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are consistent with other studies that have found a positive impact of mass media and BBC campaigns on IYCF practices (Graziose et al, ; Lee et al, ; Naugle & Hornik, ). Monterrosa et al () found increases in the consumption of leafy greens, thicker broth, and beef after the scripted message intervention, which was delivered by vaccination nurses and on local radios, was implemented in Mexico.…”
Section: Discussionsupporting
confidence: 93%
“…to date (Graziose et al, 2018), and those that have been conducted have primarily focused on exclusive breastfeeding (Flax et al, 2014;Jiang et al, 2014;Sellen et al, 2014).…”
Section: Very Few Mhealth Iycf Interventions Have Been Conducted In Lmentioning
confidence: 99%
See 2 more Smart Citations
“…In Nepal, hearing the MNP radio messages likely served as a cue to action to remind mothers to pick‐up MNP, as demonstrated by the association between hearing the radio messages and coverage indicators; however, the brevity of the radio messages was likely insufficient to support mothers in establishing and maintaining a daily routine for feeding their child MNP. A recent systematic review of nutrition education and mass media interventions found that of the 18 studies identified, only three directly assessed the impact of mass media alone, and none showed significant changes in behaviour; however, when mass media was combined with individual or group education, several interventions were able to improve IYCF practices (Graziose, Downs, O'Brien, & Fanzo, ). Other studies have also documented the importance of group counselling for improving IYCF practices generally (Flax et al, ; Nguyen et al, ; White et al, ), and one study from Peru showed that the positive encouragement from neighbours and relatives encouraged mothers to use MNPs (Creed‐Kanashiro, Bartolini, Abad, & Arevalo, ).…”
Section: Discussionmentioning
confidence: 99%